Dimensions of social learning in teacher education: An exemplary case study - van den Beemt, Antoine; Vrieling, Emmy (Proceedings of the International Conference on Networked Learning, 2016)
Growing attention can be noticed for social learning in teacher groups as a stimulus for teachers’ professional development. Research shows the importance of understanding the role and impact of informal social networks on teacher professional development. This paper describes a rich case study of student teachers, in-service teachers and teacher training educators collaborating in networks. Based on the ‘Dimensions of Social Learning (DSL)-Framework’ that includes 4 dimensions and 11 indicators of social learning, the present study observes and facilitates the social configuration of a learning group of primary (student) teachers and their educators. The purpose of the case study is 1) to translate the theoretical DSL-Framework into a form recognized by educational practice, and 2) find social configurations that support roles of (student) teachers in learning networks. The following research questions were formulated: 1) In what way can the DSL-Framework help to bring the group configuration into focus? 2) Which social configuration on dimensions and indicators supports student teachers’ role in a group together with teachers and educators? These questions are answered by video-recordings of group activities, reflective notes, the use of an online learning environment and semi-structured interviews. Data analyses were accompanied by an intervention with the purpose to translate the theoretical DSL-framework to a practice-based tool for evaluating and guiding learning networks. The research findings demonstrate that teacher groups can reflect on the learning group's social configuration by means of compiling an image with the DSL-framework. The resulting image allows teachers to analyse whether their group's configuration fits its learning goals, or that adjustments are required. In this way, professional development within teacher learning groups can be improved. Besides general recommendations for facilitating social learning in teacher groups, the study explicitly searches for ways to optimise student teachers’ role in a group of teacher experts.